Confronting Space Debris - Baiocchi, Dave; Welser, William (RAND Corporation, 2023)
Orbital space debris represents a growing threat to the operation of man-made systems in space. With the goal of guiding future mitigation or remediation efforts, this monograph examines nine comparable problems that share similarities with orbital debris: acid rain, U.S. commercial airline security, asbestos, chlorofluorocarbons, hazardous waste, oil spills, radon, email spam, and U.S. border control.